Community participation in clean and healthy living as an effort to improve the quality of health - Angreni, Wa Ode Novi; Rahagia, Rasi; Setyawati, Ari; Kamaruddin, Muh. Ihsan; Suprapto, Suprapto (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
In efforts to improve public health, it is necessary to implement clean and healthy living behaviours in the community to achieve a better standard of living. One strategy that can be used to earn a degree in public health is to provide education on public awareness of the importance of implementing a clean and healthy lifestyle. Community service activities aim to evaluate the impact of counselling on the level of knowledge and attitudes of the community related to clean and healthy living. The method involves organising counselling sessions in several communities through active community participation. We used pre-counseling and post-extension surveys to measure changes in knowledge levels and attitudes. Results showed a significant increase in people's knowledge levels after counselling. Interactive counselling sessions and clear information delivery successfully provided a better understanding of clean and healthy living principles. It concluded with the active participation of the community, the involvement of community leaders, and the use of relevant supporting materials. These findings have positive implications for developing health education programmes at the community level. Increased knowledge and attitudes are expected to change people's behaviour towards a healthier lifestyle.